Targeted resequencing of 29 candidate genes and mouse expression studies implicate ZIC3 and FOXF1 in human VATER/VACTERL association - El Maarri, Osman (2015)
The VATER/VACTERL association describes the combination of congenital anomalies including vertebral defects, anorectal malformations, cardiac defects, tracheoesophageal fistula with or without esophageal atresia, renal malformations, and limb defects. As mutations in ciliary genes were observed in diseases related to VATER/VACTERL, we performed targeted resequencing of 25 ciliary candidate genes as well as disease-associated genes (FOXF1, HOXD13, PTEN, ZIC3) in 123 patients with VATER/VACTERL or VATER/VACTERL-like phenotype. We detected no biallelic mutation in any of the 25 ciliary candidate genes; however, identified an identical, probably disease-causing ZIC3 missense mutation (p.Gly17Cys) in four patients and a FOXF1 de novo mutation (p.Gly220Cys) in a further patient. In situ hybridization analyses in mouse embryos between E9.5 and E14.5 revealed Zic3 expression in limb and prevertebral structures, and Foxf1 expression in esophageal, tracheal, vertebral, anal, and genital tubercle tissues, hence VATER/VACTERL organ systems. These data provide strong evidence that mutations in ZIC3 or FOXF1 contribute to VATER/VACTERL.